The Position of Local Self-Government in the Constitution of the Republic of Poland - Rabska, Teresa (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The paper is an English translation of Pozycja samorządu terytorialnego w konstytucji by Teresa Rabska published originally in Polish in the Journal of Law Economy and Sociology from 1995. The text is published as a part of a newly established section of the Adam Mickiewicz University devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.